STUDENTS’ MOTIVATION IN LEARNING ENGLISH AS THE FIRST FOREIGN LANGUAGE IN INDONESIA TROUGH THE ARCS - Martasari, Yustika Monika (UNIVERSITAS SLAMET RIYADI, 2018)
ABSTRACTThe goals of the research are to find out: 1) the factors that might influence students’ motivation in class VIII-E of SMP Kristen 1 Surakarta in 2016/2017 academic years. 2) To motivate the students’ in learning English in class VIII-E of SMP Kristen 1 Surakarta in 2016/2017 academic years. This researcher used case study research (single case embedded design). This case study research was conducted in SMP Kristen 1 Surakarta on September until October 2016. Data collecting techniques were observation, interview, and documentation. The analysis data, the researcher got the data from interviewing students and teacher; and observing the teacher’s method while delivering the English material. The researcher used methodological triangulation to gain the validity of the data. The ARCS is one of using suitable ways can use by teacher and school to give a good motivation to students. In this research, the researcher found that students’ in class VIII-E of SMP Kristen 1 Surakarta in 2016/2017 academic years, came from various family background; which were: 11 students who came from unsupported family and 10 students who came from supported family in learning English. Both of students’ group needed motivation to learn English as the first foreign language in Indonesia. Base on the explanation, The ARCS can use as tools to increase the students’ motivation in learning English. So, the students would interest in teaching and learning process and they could motivate themselves to be active in learning English. Keywords: Motivation, English Foreign Language, Case Study Research, ARCSmethod, ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui: 1) faktor-faktor yang dapat mempengaruhi motivasi siswa di kelas VIII-E SMP Kristen 1 Surakarta pada tahun akademik 2016/2017. 2) Untuk memotivasi siswa dalam belajar bahasa Inggris di kelas VIII-E SMP Kristen 1 Surakarta pada tahun akademik 2016/2017. Peneliti ini menggunakan penelitian studi kasus (desain kasus tunggal). Penelitian studi kasus ini dilakukan di SMP Kristen 1 Surakarta pada bulan September hingga Oktober 2016. Teknik pengumpulan data adalah observasi, wawancara, dan dokumentasi. Analisis data, peneliti mendapatkan data dari mewawancarai siswa dan guru; dan mengamati metode guru saat menyampaikan materi bahasa Inggris. Peneliti menggunakan triangulasi metodologis untuk mendapatkan validitas data. ARCS adalah salah satu dari penggunaan cara yang sesuai yang dapat digunakan oleh guru dan sekolah untuk memberikan motivasi yang baik kepada siswa. Dalam penelitian ini, peneliti menemukan bahwa siswa di kelas VIII-E SMP Kristen 1 Surakarta pada tahun akademik 2016/2017, berasal dari berbagai latar belakang keluarga; yaitu: 11 siswa yang berasal dari keluarga yang tidak didukung dan 10 siswa yang berasal dari keluarga yang didukung dalam belajar bahasa Inggris. Kedua kelompok siswa membutuhkan motivasi untuk belajar bahasa Inggris sebagai bahasa asing pertama di Indonesia. Berdasarkan penjelasannya, ARCS dapat digunakan sebagai alat untuk meningkatkan motivasi siswa dalam belajar bahasa Inggris. Jadi, para siswa akan tertarik dalam proses belajar mengajar dan mereka dapat memotivasi diri mereka untuk aktif dalam belajar bahasa Inggris. Kata kunci: Motivasi, Bahasa Asing Bahasa Inggris, Penelitian Studi Kasus, ARCSmetode,